The maximum diversification investment strategy: A portfolio performance comparison - Ludan Theron; Gary Van Vuuren (Cogent Economics & Finance, 2018)
The efficacy of four different portfolio allocation strategies is evaluated according to their absolute returns during different economic conditions over a period of 10 years. A comparison is drawn between the Most Diversified portfolio (MD) and three alternatives; a Minimum Variance portfolio, an Equally-Weighted portfolio and a Tangent (or Maximum Sharpe ratio) portfolio. The aim is to assess portfolio performance using cumulative returns, the Sharpe ratio and the daily vola- tilities of each portfolio. The four asset allocation methods are governed by multiple constraints. Although previous work has shown that MD portfolios exhibit greater diversification and a higher Sharpe ratio than other investment strategies, this was not found using developed market index data.
Keywords: C52; G11; 330; maximum diversification; portfolio risk; optimal portfolio selection; performance